2007
DOI: 10.1002/cphc.200600725
|View full text |Cite
|
Sign up to set email alerts
|

Computing the 1H NMR Spectrum of a Bulk Ionic Liquid from Snapshots of Car–Parrinello Molecular Dynamics Simulations

Abstract: We have investigated the performance of several computational protocols in predicting the NMR spectrum of a molecular ion in a complex liquid phase such as an ionic liquid. To do this, we computed the proton NMR chemical shifts of the 1-ethyl-3-methylimidazolium cation [emim](+) in [emim][Cl]. Environmental effects on the imidazolium ring proton chemical shifts are quite significant and must be taken into account explicitly. Calculations performed on the isolated imidazolium cation as well as on the [emim][Cl]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 78 publications
4
62
1
Order By: Relevance
“…[54] Despite this, the ratios between self-diffusion coefficients seem to be more accurately reproduced than for [C 4 4 ], and found that the classical model again under-predicts the experimental values by roughly one order of magnitude. [55] It is noted by the authors that the use of a non-polarisable model for the liquid may account for some of the discrepancy.…”
Section: Dynamics Of Scaled-charge Modelsmentioning
confidence: 96%
“…[54] Despite this, the ratios between self-diffusion coefficients seem to be more accurately reproduced than for [C 4 4 ], and found that the classical model again under-predicts the experimental values by roughly one order of magnitude. [55] It is noted by the authors that the use of a non-polarisable model for the liquid may account for some of the discrepancy.…”
Section: Dynamics Of Scaled-charge Modelsmentioning
confidence: 96%
“…NMR properties are calculated for all clusters at some level of theory and finally averaged. [17,18] We used this kind of protocols in our recent investigations of NMR spectra of pure ionic liquids [19,20] and α-D-glucose in water, [21] which are very complex in terms of solute-solvent interactions. However, for the latter system we noted that, although solute-solvent interactions were quite strong and specific, alkyl 1 H and 13 C chemical shifts were well correlated with experimental values without explicitly including water molecules in the NMR calculation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Isotope shifts 13 and temperature dependence of NMR parameters are experimental manifestations of such dynamical averaging effects. Traditionally, quantum-chemical simulations of NMR parameters have been common for "isolated" molecules, such as those in gases or solutions.…”
Section: Introductionmentioning
confidence: 99%